Spalling Localization on the Outer Ring of Hybrid Ceramic Ball Bearings Based on the Sound Signals - H. T. Shi; X. T. Bai; K. Zhang; Z. N. Wang; Z. M. Liu (IEEE Access, 2019)
Spalling is one of the main defects of hybrid ceramic bearings, and the localization of the spalling is hard to realize based on traditional vibration signals. This paper proposes a new localization method for spalling on the outer ring of hybrid ceramic ball bearings based on the characteristics in the sound radiation signals. The dynamic model containing the spalling is presented, and the sound radiation is obtained through the sub-source decomposition method. Cases when the spallings are located in different zones on the outer ring are studied, and the circumferential distribution of the sound radiation is analyzed in time domain and frequency domain. The localization accuracy with different indicators are compared as well as the recognition clarity, and the results are verified through experimental investigations. Results show that the spalling makes great impact on the sound radiation of the hybrid ceramic ball bearing, and the circumferential and radial distribution of the sound radiation is closely related with the location of the spalling. It is quite essential to acquire the changes of the frequency components in the sound radiation, and the radial attenuation of the amplitude of the spalling-related frequency is crucial for the accurate localization of the spalling.